Effect of sab-a banana peel as feed component on the growth of chicken,gall s gallus. - Bedia, Nadine (UPHSI, 2005)
Chickens are widely raised worldwide because they are good sources of meat and eggs. Broiler, a breed of chicken used for meat, is a very good converter of feeds into high content protein food. However, at present, local production is declining because of very expensive capital and diminishing returns. This study used banana peal as additive to Excel commercial feed at percentages of 05, 25%, 50%, 75%, and 100%. These were given to 45-day broiler chickens three times a day for one week. Fresh water with vitamins were also given everyday to ensure good health of the chickens. Results showed that the 45-days broiler chickens grew best if fed with 25% banana peal except with the 0% based on one-way ANOVA and Tukey's Test. This is due to the feed's higher crude protein and crude fat contents which could have promoted faster growth rate in terms of weight gain and feed conversion rate. It can also be noted that feed with 25% banana peel has the same effect as 0% banana peel or pure commeercial feed.